ANALISIS KOMPARASI EKSPOR MINYAK BUMIANTAR NEGARA ANGGOTA OPEC DAN NON-OPECPERIODE 2013-2015 - Ana Fitria (Perpustakaan Universitas Surabaya, 2018)
International trade with petroleum commodities of special concern to every country producing oil. The revenue contribution of the petroleum trade very calculated, as in some Middle Eastern countries the contribution of the petroleum trade to GDP reached 60%. OPEC as an international cartel of petroleum exporting countries to set quotas petroleum sales to the international market for its member countries and set the price of petroleum in the international market have an impact on the world oil price conditions. Joined the OPEC Member countries turns petroleum exporter gets some benefits such as technology transfer and FDI (Foreign Direct Investment). In this study assessed the presence or absence of difference in the amount of petroleum Exports and Market Share of petroleum exporting countries which are members of OPEC and non-OPEC through comparative analysis using test equipment and test different variants of the mean. In the discussion it can be seen that the amount of Exports and Market Share of petroleum exporting countries belonging to a Member of OPEC and Non-OPEC there was no difference. Furthermore, identified through economic analysis of no differences in test results of variables describing the real condition of domestic petroleum needs cannot be met by local production, causing balances between demand and supply, renewable energy breakthrough is the answer to these conditions.